Impact of Patient Age on the Frequency of Urethrocutaneous Fistula After Hypospadias Repair Using Autologous Platelet-Rich Fibrin - Ghazi, Waqar Hameed (Indus Journal of Bioscience Research, 2025)
Background: Urethrocutaneous fistula (UCF) remains the most common complication after hypospadias repair. Autologous platelet-rich fibrin (PRF) has emerged as a biological sealant to improve surgical outcomes. However, the impact of patient age on UCF formation despite PRF use remains under-explored. Objective: To determine the frequency of urethrocutaneous fistula in children aged 1–6 years versus 7–12 years undergoing hypospadias repair with PRF as an intermediate layer. Methods: This was a prospective observational study conducted over 12 months at the Department of Pediatric Surgery, Services Hospital, Lahore. A total of 139 male patients undergoing primary hypospadias repair were included. Patients were divided into two groups based on age: Group A (1–6 years, n=87) and Group B (7–12 years, n=52). All surgeries utilized the tubularized incised plate (TIP) urethroplasty technique with PRF application between the neourethra and skin. Patients were followed for 3 months postoperatively for development of UCF. Data were analyzed using SPSS 25.0, and chi-square test was applied to determine statistical significance (p